If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying sqrt(14x + -6) = x + 3 Reorder the terms: qrst(-6 + 14x) = x + 3 (-6 * qrst + 14x * qrst) = x + 3 (-6qrst + 14qrstx) = x + 3 Reorder the terms: -6qrst + 14qrstx = 3 + x Solving -6qrst + 14qrstx = 3 + x Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Reorder the terms: -3 + -6qrst + 14qrstx + -1x = 3 + x + -3 + -1x Reorder the terms: -3 + -6qrst + 14qrstx + -1x = 3 + -3 + x + -1x Combine like terms: 3 + -3 = 0 -3 + -6qrst + 14qrstx + -1x = 0 + x + -1x -3 + -6qrst + 14qrstx + -1x = x + -1x Combine like terms: x + -1x = 0 -3 + -6qrst + 14qrstx + -1x = 0 The solution to this equation could not be determined.
| y^2-10y-8x-9=0 | | 6c+2-5c=-24+8 | | 9y+12x=294 | | -1/4(12x-20y) | | 6x10^4/3x10^2 | | x+1x-30=Y | | A^2-15a-54=0 | | A^3b^-5/A^-5b^3 | | 10.00+.10m=.35m | | 2n^2+2n-7=0 | | 2x+13=52 | | 11-2(3b+1)= | | 170+x=-340 | | 1.8a=6+2.25a | | -6x=2y+3 | | 4y=0x+28 | | 49=6x+13 | | 99-m=299 | | 6x=-2y-3 | | -6x=-2y-3 | | 37=6x+13 | | -4/x^2x=1/x-2 | | -51x=65 | | -51x=62 | | x-9+2x=12 | | (5)/(9)a=6+(4)/(9)a | | 5/7*42 | | 10-1(x+5)+3x=6x-5(x-1)-3 | | .02-.05+.3x=-.68 | | 68-60x=82 | | 14z-5=2z-65 | | 1/5(10x-1)=5 |